Discrimination against Migrants in Austria: An Experimental Study - Doris Weichselbaumer (Institute for the Study of Labor (IZA), 2015)
This paper experimentally examines the employment opportunities of Austrians with and without migration background who apply to job openings. Previous experiments have indicated ethnicity via the name of an applicant, however employers may not always correctly perceive this signal. This study uses a novel approach to signal ethnic background and employs carefully matched photos as distinct visual cues. While results document employment discrimination for all groups with migration background, it is most pronounced for applicants with an African background. To explain why and when discrimination occurs, a battery of firm and job specific characteristics are examined. These, however, help little to explain the level of employment discrimination in Austria.
Keywords: C93; J15; J71; 330; migration; discrimination; hiring; correspondence testing